2019
DOI: 10.1038/s41375-018-0360-1
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell constitution in bone marrow microenvironment predicts outcome in adult ALL

Abstract: As novel immunological treatments are gaining a foothold in the treatment of acute lymphoblastic leukemia (ALL), it is elemental to examine ALL immunobiology in more detail. We used multiplexed immunohistochemistry (mIHC) to study the immune contexture in adult precursor B cell ALL bone marrow (BM). In addition, we developed a multivariate risk prediction model that stratified a poor survival group based on clinical parameters and mIHC data. We analyzed BM biopsy samples of ALL patients (n = 52) and healthy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 54 publications
1
54
0
Order By: Relevance
“…[11][12][13][14] However, unlike in solid tumors, the clinical efficacy of immune checkpoint inhibition, particularly PD-1 inhibitor monotherapy, appears to be limited in AML, MDS, and multiple myeloma (MM), [15][16][17][18] which may be due to the complexity of the leukemic bone marrow (BM) microenvironment in which persistent stimulation of leukemia cell-derived antigen results in more complex T-cell exhaustion and dysfunction. [19][20][21] In this case, more than one immune inhibitory receptor may contribute to T-cell dysfunction. The heterogeneity of exhausted T cells may be a reason for the lower effects of PD-1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] However, unlike in solid tumors, the clinical efficacy of immune checkpoint inhibition, particularly PD-1 inhibitor monotherapy, appears to be limited in AML, MDS, and multiple myeloma (MM), [15][16][17][18] which may be due to the complexity of the leukemic bone marrow (BM) microenvironment in which persistent stimulation of leukemia cell-derived antigen results in more complex T-cell exhaustion and dysfunction. [19][20][21] In this case, more than one immune inhibitory receptor may contribute to T-cell dysfunction. The heterogeneity of exhausted T cells may be a reason for the lower effects of PD-1 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the tumor microenvironment can lead to identification of novel therapeutic targets. Previous studies have shown that development of B-ALL alters immune cell constitution and the BMM 9,[28][29][30] . In this study, we dissected responses of normal bone marrow immune cells during early stages of B-cell leukemia development at a single-cell level.…”
Section: Discussionmentioning
confidence: 99%
“…Co-culturing M2-macrophages with T-ALL cell in vitro significantly induced leukemic cell proliferation via C5a, TNFα, growth-related oncogene (GRO)-α and IL-6 [22]. Hohtari et al analyzed immune cell constitution in adult precursor B cell ALL bone marrow (BM), demonstrating increased proportion of M2-like macrophages and myeloid-derived suppressor cells (MDSCs) in ALL patients' BM compared to healthy patients [23].…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%